USA Child (0-4) and Adult (55-74) Mortality and % GDP-Health Expenditure and the Other Western Countries 1989-2015. America needs an "National Neighbourhood Health Service" - Colin Pritchard; Emily Rosenorn-Lanng; Richard Williams (Archives of Community Medicine and Public Health - Peertechz Publications, 2019)
Purpose: To analyse how effective was the USA, compared to Other Western Countries (OWC) in reducing premature deaths 1989-2015. Design: This population-based study is a cost-effective model of fiscal input into health related to clinical outputs, recognising socio-economic factors influence health outcomes. Using World Bank data for total % GDP-Expenditure-on-Health, and, WHO data for Child (0-4), Adult (55-74) and Age-Standardised-Death-Rates rates per million America is compared with OWC. Cost-Effective Ratios (CEF) are calculated and Confidence Intervals (95%) tests USA against each OWC. `Excess' deaths are calculated between the most and least expensive health systems. Setting: Twenty Other Western countries. Patients: National populations. Outcomes: USA highest current total %GDPEH 16.8% and highest average of 12.7% and UK lowest 7.1% over period. USA Child (0-4) highest at 1249pm, OWC averaged 803pm. Fourteen countries had significantly bigger reductions than America. USA Adult (55-74) mortality was highest at 12,554pm, OWC averaged 9,835pm. Fourteen countries had significantly bigger reductions than USA. Excess Deaths: America failed to match UK total mortality rates yielding 488,273 excess deaths, of which 12,613 were children. Cost-Effectiveness-Ratio: America had smallest CER 1:113, OWC averaged 1:270, an USA to OWC ratio of 1:239. UK CER was 1:323 producing a USA: UK ratio of 1:2.86. Conclusion: America's health system more expensive as Britain's and significantly less effective than most OWC. The USA needs to change its socio-economic political mind set' if it is to match the <span id="MathJax-Element-1-Frame" class="mjx-chtml MathJax_CHTML" tabindex="0" data-mathml="<mstyle displaystyle="true">halfprice’NHS<mspace width="1ex" ></mspace><mtext>and</mtext><mspace width="1ex" ></mspace>move→wardsanAmericansty≤</mstyle>" role="presentation" style="font-size: 119%; position: relative;">halfprice'NHSandmove→wardsanAmericans<span class="mjx-char MJXc-TeX-math-I" style="padding-top: 0.423em; padding-bottom: